HUBUNGAN PENGHASILAN KELUARGA DENGAN MINAT MENGIKUTI PROGRAM PELATIHAN DI PKBM AL MUSTAJAB BANTUL YOGYAKARTA - Thesa Ikhtiyarini Putri (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2016)
This study aimed to know (1) familysalary, (2) interest in following life skill program, and (3) correlation between family salary and interest in following life skill program.The type of this study was ex-post facto. Datacollection methods used questionnaires anddocumentation. Data analysis technique used adescriptive analysis and hypothesis testing byusing Product Moment that was started by normality and linearity test. This study shows thatthe family salary was in enough category withrelative frequency 48.33% and the interest infollowing life skill program was in enough category with relative frequency 50%. The scoreof robs was 0.616 above rtable 0.254 (robs = 0.616> rtable 0.254). It means that there was a positive and significant correlation between familysalary and interest in following life skill program. The score of determinant coefficient (R2)was 0.379, it means that the family salary gavea positive contribution 37.9% toward interestin following life skill program, while 62.1%was influenced by other factors that were notanalyzed in this study